(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Obsessive-compulsive Disorder (OCD) is a chronic disabling psychological condition, which can severely affect quality of life (QOL). Growing interest has been dedicated to assessing which domains of QOL are more severely affected in patients with OCD. However, research yielded conflicting findings. Investigating QOL in OCD could suggest the need for integration of interventions aimed at improving those specific domains more severely impaired by obsessions and compulsions. Methods. We will conduct a systematic review of cross-sectional case-control studies according to PRISMA guidelines, where patients with a primary OCD diagnosis were compared on QOL outcomes with healthy controls. Primary objectives will be to examine differences in QOL outcomes between patients with OCD and healthy controls, and to assess which QOL domains are more severely impaired in patients compared with controls, particularly subjective well-being, social and interpersonal functioning, work functioning, and family functioning. Subsequently, the study will investigate potential moderators of QOL in OCD, including participants characteristics (age, sex, presence of comorbid personality disorders, OCD symptom severity, severity of concurrent depressive symptoms, duration of OCD symptoms, and generational cohort), and study characteristics (date of publication and methodological quality of the studies). Online databases will be searched (PsycINFO, PubMED, Science Direct, Cinahl, Biological Abstracts, Psyclit, Embase, The Cochrane Central Register of Controlled Trials, and Google Scholar). To locate unpublished records, conference abstracts, doctoral dissertations and theses will be handsearched, and experts will be contacted. Statistical analyses will be performed though random effect model meta-analysis. Risk of bias assessments will be conducted using the instrument Methodological Index for Non-Randomized Studies.